2009
DOI: 10.1093/ageing/afp068
|View full text |Cite
|
Sign up to set email alerts
|

Detection of MCI in the clinic: evaluation of the sensitivity and specificity of a computerised test battery, the Hopkins Verbal Learning Test and the MMSE

Abstract: overall, we conclude that the HVLT has better sensitivity for the detection of MCI in older adults than the CogState, but that CogState may enable the identification of cognitive deficits above and beyond impairments in memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
113
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 29 publications
4
113
1
Order By: Relevance
“…In total, 16 studies [68][69][70][71][72][74][75][76][77][78][79][80][81]83,85,86 were included in the diagnostic accuracy review.…”
Section: Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 16 studies [68][69][70][71][72][74][75][76][77][78][79][80][81]83,85,86 were included in the diagnostic accuracy review.…”
Section: Included Studiesmentioning
confidence: 99%
“…Five studies reported results for more than two groups of participants: three included healthy controls, MCI and early dementia, 71,76,86 and two included healthy controls, early dementia and early dementia/MCI combined. 70,74 In total, 10 studies 68,69,71,72,75,76,78,79,85,86 evaluated the use of automated computerised tests to detect MCI alone, seven studies 70,71,74,76,80,81,86 reported results for early dementia, three studies 70,74,77 reported results for combined MCI/early dementia and one study 83 reported results for human immunodeficiency virus (HIV)-associated neurocognitive disorder (HAND).…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cogstate brief battery, a computerized series of neuropsychological tests [5], has demonstrated good validity and high test-retest reliability in cognitively normal older adults as well as those with mild cognitive impairment (MCI) or dementia [5][6][7][8]. The Cogstate battery is also sensitive enough to detect subtle cognitive decline over 12 months in a population of older adults with MCI [9] and to differentiate between normal cognitive function, MCI, and Alzheimer's disease [6].…”
Section: Hhs Public Accessmentioning
confidence: 99%
“…However, task comprehension will likely improve in future cohorts as computer literacy increases in older adults [20]. Additionally, although prior studies of the Cogstate battery in older adults demonstrate good correlation with performance on other neuropsychological test instruments [8,21], the Cogstate battery may not adequately measure some cognitive domains such as executive functions or semantic and verbal fluency. …”
mentioning
confidence: 99%